KINERJA KEUANGAN DAERAH KABUPATEN KONAWE SELATAN - Salifa, Salifa (JIM : Journal Of International Management, 2023)
This research is entitled State and Regional Finance Performance of South Konawe Regency. This study aims to determine the State and Regional Financial Performance of South Konawe Regency. The data analysis method is descriptive analysis, with the ratio of financial independence analysis, the degree of fiscal decentralization of South Konawe Regency from 2016 to 2020. The results of the study are Effectiveness can be concluded that the effectiveness of local taxes in the period 2016-2020 has increased. So based on the criteria or indicators of effectiveness, it can be said that the effectiveness of local taxes in South Konawe Regency is categorized as very effective so that this shows that the Regional Financial Management Agency of South Konawe Regency is very effective in managing local taxes, the contribution of local taxes has been done it appears that in the period 2016-2020 it is very good. In 2017 the contribution was the largest at 96.91% and in 2018 it had the smallest contribution rate at 68.38%. The average percentage of Local Tax Contribution to Local Revenue from 2016-2020 is 80.41%, which is included in the Very good category because it is above 50%.